Sistem Keamanan Berlapis Menggunakan Metode Access Control List Dan Enkripsi Source Code Pada Web Login - Kamarudin, Kamarudin; Gazali, Mukhaimy (Jurnal Teknologi Informasi (JUTECH), 2021)
Web documents are the most important assets for organizations to represent reports managed by servers. Meanwhile, the form is the entrance for the input provided by the user to be able to take advantage of server resources, be it a database, or other features that are owned by the server. This research focuses on the security of the web login form which is the entry point for various users. The level of authority (authorization) of users is set based on the Access Control List (ACL) which is arranged in such a way by the administrator. Multi-layered security goes through several stages that must be passed by the user, from validation, verification, authentication to authorizing according to the rights given to him by the administrator. The results found provide more value for web developers to set a standard security system for the web login form they build. However, various other security opportunities may be found in subsequent research, as developments